The Influence of Relational Marketing and Brand Image on Customer Loyalty Mediated by Patient Experience - Mashudani, Lizda; Dewi, Sandra; Nofierni, Nofierni (Eduvest - Journal of Universal Studies, 2025)
Background: Based on a preliminary survey, it was found that there are still problems in: patient loyalty, complaint handling, and suboptimal communication in the outpatient installation service of dr. Sitanala General Hospital Tangerang. Research Objective: aims to analyze the direct and indirect effects of relational marketing and brand image on customer loyalty with patient experience as an intervening variable. Research Method: This quantitative study uses an explanatory method with a cross-sectional design. Data were collected from 119 patients of the Outpatient Installation of dr. Sitanala General Hospital Tangerang, who had been treated at least twice. Data analysis used Structural Equation Modeling - Partial Least Squares (SEM-PLS). Research Results: Shows that the brand image variable is the variable that has the most positive and significant effect on customer loyalty in the outpatient installation of dr. Sitanala General Hospital Tangerang. While patient experience partially mediates (complements) the effect of relational marketing and brand image on customer loyalty. In a managerial context, this study can be a basis and reference for hospitals on the importance of creating and building a positive and strong brand image consistently and continuously in order to form a positive and strong patient perception in order to achieve customer loyalty. In addition, it is also necessary to make efforts to improve the quality of interactions with patients and strive to achieve a positive patient experience.